A study on ester thiosemicarbazones - (:unkn) unknown (My University, 1997)
The cyclization of ester thiosemicarbazones to two different heterocycles was studied for some new thiosemicarbazones, and only the formation of 1,2,4-triazol-5-thiols was attributed to the regioselectivity of the ring closure reaction, due to a steric hindrance of bulky groups. Next, some of the new compounds were tested for their in vitro antimicrobial and antitumor activities.
Keywords: 1,2,4-triazol-5-thiols; 1,3,4-thiadiazoles; 4,5-dihydro-1h-1,2,4-triazol-5-thiones; Biological activity; Ester thiosemicarbazones; Synthesis